Brain Abscess and Esophageal Dilatation: Where is the Link? - Case Report - Welling, Leonardo C.; Feltrin, Fabricio Stewan; Welling, Mariana S.; Brino, João Afonso Caldeira; Zyto, Victor Feferbaum; Figueiredo, Eberval G. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction Caustic substance ingestion is a common cause of esophageal stricture in children. The primary treatment is esophageal dilatation. Although it is known that endoscopic esophageal dilatation is a procedure associated with a high rate of bacteremia, current guidelines do not recommend routine throat swab cultures or antibiotic prophylaxis for the general children population.Case Report We describe a case of a 7-year-old boy presenting with refractory headaches who was diagnosed with cranial abscess after multiple esophageal dilatations due to stenosis caused by caustic soda ingestion. The patient was subjected to neurosurgical intervention and intravenous antibiotic treatment for 6 weeks. Streptococcus viridans culture was positive in purulent abscess content.Conclusion We highlight this condition that, although rare, needs immediate diagnosis and proper treatment. We also recommend routine testing of throat swabs and antibiotics prophylaxis to children undergoing esophageal dilatation.
Keywords: brain abscess; esophageal stenosis; endoscopy